Effects of genetic variations in the Adiponectin pathway genes on the risk of colorectal cancer in the Chinese population - He, Bangshun (BioMed Central, 2011)
BACKGROUND: Decreased expression of adiponectin (ADIPOQ) is associated with an increased risk for developing colorectal cancer (CRC) in humans. This study was designed to determine whether polymorphisms present in the ADIPOQ and its type 1 receptor (ADIPOR1) could affect the risk of CRC. METHODS: We measured five polymorphisms in the ADIPOQ and two polymorphisms in ADIPOR1, and analyzed their associations with CRC risk in 420 CRC patients and 555 age- and gender-matched healthy individuals. RESULTS: Multivariate logistic regression analyses revealed that the CRC risks (adjusted odds ratio and 95% confidence interval) associated with the ADIPOR1 genotypes were 0.53 (95% CI, 0.35-0.81) for rs12733285C/T, 0.59 (95% CI, 0.45-0.78) for rs1342387A/G, and 0.59 (95% CI, 0.39-0.89) for rs1342387A/A, respectively. Furthermore, the risks were more significant in carriers of the allele A of rs1342387A/G (adjusted OR, 0.59; 95% CI, 0.46-0.77) than noncarriers (G/G). In a further subgroup analysis, we observed that rs266729G/C was associated with an increased risk for colon cancer (adjusted OR, 1.50; 95% CI, 1.05-2.14) but not for rectal cancer (adjusted OR, 0.88; 95% CI, 0.63-1.22), and that carriers of the G allele had an increased risk for developing colon cancer (adjusted OR, 1.45; 95% CI, 1.03-2.05). CONCLUSIONS: We conclude that the rs12733285C/T genotype and the carriage of the A allele of rs1342387 (A/G or A/A) in ADIPOR1 are the protective factors for CRC, while that rs266729G/C and G allele of ADIPOQ are the risk factors for colon cancer after excluding rectal cancer cases.